Peces de la Laguna Cormorán, Parque Nacional Sangay, Ecuador - Fernando Anaguano-Yancha (ACI Avances en Ciencias e Ingenierías, 2017)
Abstract I conducted a fish inventory at the Cormoran Lagoon, in the icthyogeographic area Upano–Zamora, during October 2011 (dry season), February 2012 (transition period), and May 2012 (rainy season). Fish were sampled using four trammels (20 m length, 1.5 m height), 40 fishing lines, and a hand net. A total of 599 individuals of 16 species and six families were captured. The order Characiformes was the most abundant and diverse, and Lebiasina elongata (Lebiasinidae) and Astyanax fasciatus (Characidae) were the most abundant species. Species abundance gradually decreased as the rainy season arrived. Elevational ranges of the genus Chaetostoma (Chaetostoma microps) and of the family Heptapteridae (Rhamdia quelen) are increased to 1783 m in Ecuador. Fish diversity at Cormoran Lagoon still needs more studies. It is necessary to carry out taxonomic, ecological, and biogeographic studies that contribute to the knowledge of fish diversity in this tropical aquatic ecosystem. It is posible that some species are endemic, specially in the genera Astroblepus and Bryconamericus.    Resumen Se realizó un inventario de peces en la laguna Cormorán, en la zona ictiogeográfica Upano–Zamora, durante octubre 2011 (época de seca), febrero 2012 (época de transición) y mayo 2012 (época de lluvias). Los peces fueron muestreados usando cuatro trasmallos (20 m de largo, 1,5 m de alto), 40 anzuelos y una red de mano. Un total de 599 individuos de 16 especies y seis familias fueron capturados. El orden Characiformes fue el más abundante y diverso, y Lebiasina elongara (Lebiasinidae) y Astyanax fasciatus (Characidae) fueron las especies más abundantes. La abundancia de especies disminuyó paulatinamente conforme llegaba la época de lluvias. Se extienden los rangos altitudinales del género Chaetostoma (Chaetostoma microps) y de la familia Heptapteridae (Rhamdia quelen) hasta 1783 m en Ecuador. La ictiofauna de la laguna Cormorán todavía necesita mayores de estudios. Es necesario realizar estudios taxómicos, ecológicos y biogeográficos que contribuyan al conocimiento de la diversidad de peces de este ecosistema acuático tropical. Es posible que algunas especies encontradas en este estudio sean endémicas, especialmente en los géneros Astroblepus y Bryconamericus.